Heterogeneous single-site synergetic catalysis for spontaneous photocatalytic overall water splitting. Issue 18 (15th April 2019) - Su, Hui; Liu, Meihuan; Cheng, Weiren; Zhao, Xu; Hu, Fengchun; Liu, Qinghua
Abstract : Heterogeneous Pt1 N x –Au1 N x redox single sites anchored on a g-C3 N4 support were designed for high-efficiency spontaneous photocatalytic overall water splitting. Abstract : The development of photocatalysts with synergetic bifunctional catalytic centers is of great importance for efficient photocatalytic water splitting towards sustainable conversion and storage of renewable solar energy. Here, we present a conceptual design of atomic-level bifunctional redox single sites to realize an efficient catalytic reaction of photoexcited electron–hole pairs on g-C3 N4 -based photocatalysts for spontaneous overall water splitting. The atomically dispersed heterogeneous Pt1 N x –Au1 N x redox single sites anchored on a g-C3 N4 support could successfully introduce p–n coupled micro-domains as effective bifunctional electron-donor–acceptor centers, which significantly improves the electron–hole separation efficiency to ∼60% in the visible-light region of 400–450 nm which is 6–10 times that of individual Pt/C3 N4 and Au/C3 N4 . The bifunctional Pt–Au/C3 N4 single-site photocatalyst could thus effectively split pure water with a reduced surface redox reaction barrier by ∼300 mV, resulting in ∼10-fold enhancement of the photocatalytic performance.